Preparation method and application of heterogeneous E-Fenton cathode material

By loading graphene on nickel foam, a graphene-loaded nickel foam E-Fenton cathode material was prepared, which solved the problems of low degradation efficiency of traditional E-Fenton technology under neutral and alkaline conditions and easy corrosion of cathode materials, and achieved It achieves efficient E-Fenton reaction and anti-corrosion effect under wide pH conditions.

CN119330465AActive Publication Date: 2025-01-21CHONGQING THREE GORGES UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411460952.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Traditional E-Fenton technology is difficult to effectively degrade organic pollutants under neutral and alkaline conditions, and cathode materials are prone to corrosion when air contact, limiting their application range.

Method used

Graphene was loaded on nickel foam through electrophoretic deposition technology to prepare a graphene-loaded nickel foam E-Fenton cathode material, achieving efficient E-Fenton reaction under wide pH conditions without adding Fe ions.

Benefits of technology

This method significantly improves the removal rate of organic dyes under neutral conditions, avoids the addition of Fe ions and H2O2, reduces secondary pollution, and improves the anti-corrosion performance of cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330465A_ABST
    Figure CN119330465A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a heterogeneous E-Fenton cathode material, nickel foam (NF) and graphite oxide (GO) are used as raw materials, a graphene-loaded NF (GA-NF) electro-Fenton cathode material is obtained through the steps of acid pickling, electrophoretic deposition, hydrothermal reduction, vacuum drying and the like, an efficient E-Fenton process can be achieved under the wide pH condition without adding Fe ions, and secondary pollution is avoided. The heterogeneous E-Fenton cathode material prepared by the method can break through the limitation of traditional E-Fenton, the 30-min removal rate of organic dye (RhB) under the neutral condition reaches 99% or above, the heterogeneous E-Fenton cathode material has the advantages of being high in reaction activity, good in treatment effect and the like, addition of Fe ions and hydrogen peroxide is not needed, and no iron mud is generated in the reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an electrode material, and in particular to a method for preparing a heterogeneous E-Fenton cathode material and application thereof. Background Art

[0002] Fenton oxidation to remove organic matter based on added H2O2 and catalyst Fe 2+ The generated hydroxyl radicals (·OH) with strong oxidizing ability can achieve the degradation and even mineralization of organic pollutants. However, H2O2, which is highly corrosive and oxidizing, has serious transportation and storage safety issues, which brings higher processing costs and operational risks to the Fenton oxidation removal of organic matter. In recent years, in order to further develop Fenton oxidation, the electro-Fenton (E-Fenton) technology has emerged. The basic principle of the reaction of the E-Fenton technology is that O2 is reduced to H2O2 at the cathode and reacts with Fe 2+ The reaction generates ·OH with strong oxidizing properties, thereby achieving oxidative degradation of pollutants. The generation mechanism of ·OH in E-Fenton technology is to generate Fe 2+ and H2O2, and then generate ·OH. In the E-Fenton technology, the generation of ·OH is a key step, which determines the efficiency of the technology in degrading organic matter. Specifically, water molecules are oxidized at the anode to produce a small amount of ·OH, while in the acidic medium, the cathode reduces oxygen to hydrogen peroxide (H2O2). These reaction processes involve H2O2 and Fe generated by electrochemical methods. 2+ As a continuous source of Fenton reagent, the generation efficiency of ·OH is improved. The traditional Fenton reaction also uses H2O2 as a chain propagation medium through Fe 3+ / Fe 2+ However, the E-Fenton technology achieves this process through electrochemical reaction, which improves the efficiency and controllability of the reaction.

[0003] The mechanism of action of OH in E-Fenton technology is mainly to degrade organic matter through strong oxidation. OH has extremely strong oxidizing ability, and its redox potential is as high as 2.8V, second only to fluorine, which makes it able to effectively degrade most organic pollutants. 2+In the presence of ·OH, ·OH is generated and a series of chain reactions are initiated. These reactions include not only the direct oxidation of ·OH, but may also involve the generation of other active oxygen species, which act together on the degradation process of organic matter. The characteristic of this chain reaction is that once it starts, it can continue until the reactants are completely degraded or the reaction conditions change. Therefore, the E-Fenton technology achieves efficient degradation of organic matter by continuously generating ·OH, and finally converts it into harmless small molecules, such as H2O and CO2, thereby achieving the purpose of purifying water quality. E-Fenton requires the addition of homogeneous Fe 2+ However, under neutral and alkaline conditions, the Fe 3+ Iron sludge precipitation is inevitable, making it difficult for the H2O2 produced on the surface of the cathode material to react with Fe in the solution. 2+ The catalytic reaction to form ·OH makes the E-Fenton oxidation method unsuitable for wastewater treatment in a wide pH range (usually the most suitable pH is ≈ 3).

[0004] Therefore, developing a heterogeneous E-Fenton cathode material with a wide pH range, especially suitable for near-neutral or alkaline conditions, and capable of efficiently producing OH in situ on the electrode surface is beneficial to the promotion and application of E-Fenton technology for wastewater treatment. Summary of the invention

[0005] Studies have shown that heterogeneous Fenton can avoid the limitations of homogeneous Fenton processes when the Fenton catalyst is dispersed on a substrate in the form of iron-containing nanoparticles. In order to overcome the limitations of homogeneous Fenton technology, heterogeneous Fenton technology has been widely studied, and a higher demand has been put forward for the development and utilization of recyclable and highly stable solid-phase catalyst heterogeneous E-Fenton materials. Different porous solid supports, including activated carbon, zeolites and biochar, and various synthesis methods such as precipitation, sol-gel, wet impregnation and adsorption have been used to synthesize effective heterogeneous catalysts in EF systems. Due to the limitations of heterogeneous catalysts such as low conductivity, high synthesis cost, strong aggregation and difficulty in agglomeration of suspended particles, their application in practical engineering applications may not be easy. In the past few years, catalyst particles have been attached to highly porous electrodes to increase the volume ratio of electrode surface to electrolyte, solve the limitation of mass transport, and improve the performance of EF in removing pollutants at neutral and near-neutral pH values. In the heterogeneous EF process, H2O2 can be generated through the selective oxygen reduction reaction (ORR), which contains two types of reaction pathways: (i) - The reduction-dominated reaction and (ii) 4e as a competing reaction - The catalytic efficiency of heterogeneous iron-based catalysts for the decomposition of H2O2 to ·OH depends on the number of exposed active sites in the catalyst and the Fe3+ Fe 2+ The conversion rate of H2O2 is determined by the production and catalytic effect of H2O2, and the performance of the cathode and even the entire system is determined. Therefore, the cathode plays a key role in the in-situ heterogeneous electrofocusing system. The heterogeneous E-Fenton method has significant advantages such as expanding the working pH value, preventing iron ion leaching, and improving catalyst stability and reusability.

[0006] In addition, when the E-Fenton cathode material is used to treat wastewater, the metal surface is very susceptible to corrosion. The purpose of corrosion prevention is achieved by loading graphene on its surface. Among various surface protection technologies, electrophoretic deposition (EPD) is conducive to the preparation of an ideal uniform coating. And because of its low cost and easy control, EPD is widely used to deposit composite coatings on conductive substrates, which can significantly improve the wear resistance and working life of the material. As an emerging two-dimensional structure, graphene and graphene oxide exist in the form of sp2 carbon hybrid networks and have attracted widespread attention due to their excellent chemical inactivity, excellent strength and enhanced resistance to erosive environments, easy shearing and good lubrication properties. In different substantial applications such as energy storage, field emission devices, solar cells, etc., the use of graphene with controllable properties is highly required.

[0007] Taking the above considerations into consideration, this study aims to prepare graphene-loaded nickel foam E-Fenton cathode by electrophoretic deposition technology to solve the problems of the existing E-Fenton reaction, such as the need for external addition of H2O2, the need for external addition of Fe ions, the generation of iron sludge under neutral and alkaline conditions that affects the reaction efficiency and causes secondary pollution, the narrow pH range, and the easy corrosion of iron cathode materials in contact with air.

[0008] In view of the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing a heterogeneous E-Fenton cathode material and its application. The preparation method of the present invention uses nickel foam (NF) and graphite oxide (GO) as raw materials, and obtains graphene-loaded NF (GA-NF) electro-Fenton cathode material through acid washing, electrophoretic deposition, hydrothermal reduction, vacuum drying and other steps. It can realize an efficient E-Fenton process under a wide pH condition without adding Fe ions, and does not produce secondary pollution. The specific process is as follows:

[0009] The present invention first discloses a method for preparing a heterogeneous E-Fenton cathode material, comprising:

[0010] (1) placing the nickel foam sheet in an acetone solution for ultrasonic treatment, and then immersing it in a 10% H2SO4 solution for acid washing; finally, ultrasonically cleaning it with deionized water, and vacuum drying it to obtain a pretreated nickel foam sheet for use;

[0011] (2) using deionized water as a dispersion medium for graphite oxide to prepare a graphite oxide suspension for later use;

[0012] (3) using the pretreated nickel foam sheet as a cathode, placing parallel platinum sheets of equal area on both sides of the cathode, and performing cathode electrophoretic deposition with a DC power supply at a constant voltage to prepare a nickel foam sheet loaded with graphite oxide;

[0013] (4) The nickel foam sheet loaded with graphite oxide is transferred to a polytetrafluoroethylene reactor with a volume of 100 ml and filled with ethylene glycol solution, and after high-temperature reduction, it is repeatedly washed with deionized water to obtain a heterogeneous E-Fenton cathode material.

[0014] Furthermore, the size of the nickel foam sheet in step (1) is 10 mm×20 mm×2 mm; the ultrasonic treatment time in the acetone solution is 20 min; and the pickling time in the H2SO4 solution is 5 min.

[0015] Furthermore, the deionized water ultrasonic cleaning in step (1) is performed 3 times, and each cleaning time is 10 minutes.

[0016] Furthermore, the concentration of the graphite oxide suspension in step (2) is 0.2 mg / ml.

[0017] Furthermore, the size of the platinum sheet in step (3) is 10 mm×20 mm×1 mm.

[0018] Furthermore, in step (3), the constant voltage is 140 V and the deposition time is 15 min.

[0019] Furthermore, the high temperature reduction temperature in step (4) is 140° C., and the reduction time is 14 h.

[0020] The present invention also discloses a heterogeneous E-Fenton cathode material prepared according to any of the above preparation methods.

[0021] The present invention also discloses an application of the heterogeneous E-Fenton cathode material in treating refractory high molecular organic pollutants.

[0022] Furthermore, the application includes:

[0023] In the application process of treating difficult-to-degrade high-molecular organic pollutants, the heterogeneous E-Fenton cathode material is used as the cathode, oxygen or air is introduced near the cathode, and the inert electrode is used as the anode. The treatment object is sewage or soil containing organic pollutants, and an electrolyte solution with a pH of 3 to 8 is added to treat the organic pollutants by direct current electrolysis.

[0024] Furthermore, the electrolyte solution is a sodium salt or potassium salt electrolyte solution.

[0025] Furthermore, the electrolyte solution is one or more of sodium sulfate, sodium acetate or sodium nitrate.

[0026] Furthermore, the electrolyte solution is one or more of potassium sulfate, potassium acetate or potassium nitrate.

[0027] Furthermore, the refractory high molecular organic pollutants include but are not limited to: phenol, norfloxacin, sodium dodecylbenzene sulfonate, and p-nitrophenol.

[0028] Furthermore, the oxygen or air introduction rate is 0.1-3.0 L / min; the voltage of direct current electrolysis is 2-8V.

[0029] The beneficial effects of the present invention are:

[0030] (1) GO was successfully loaded on NF by electric field drive, and then a graphene-loaded NF cathode material that can be used to treat organic wastewater using the E-Fenton technology was prepared by hydrothermal reduction.

[0031] (2) The loading of graphene can achieve a certain anti-corrosion effect and improve the degradation performance of nickel foam.

[0032] (3) GO-loaded nickel foam as the cathode material of the E-Fenton treatment system has a good degradation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of nickel foam before graphene loading;

[0034] Figure 2 This is the SEM image of graphene loaded with nickel foam;

[0035] Figure 3 This is a SEM / mapping combination image of graphene-loaded nickel foam;

[0036] Figure 4 This is the mapping diagram of graphene-loaded nickel foam, where a represents the distribution of nickel elements and b represents the distribution of carbon elements;

[0037] Figure 5 This is the RhB removal rate curve before and after loading of nickel foam electro-Fenton cathode. DETAILED DESCRIPTION

[0038] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.

[0039] Example 1

[0040] A method for preparing a heterogeneous E-Fenton cathode material, comprising:

[0041] (1) The NF sheet (10 mm × 20 mm × 2 mm) was placed in an acetone solution for ultrasonic treatment for 20 min; then it was immersed in a 10% H2SO4 solution for pickling for 5 min to slightly corrode it, so as to ensure that the cracks and porous structure on the NF surface and the hydroxyl groups on the surface are more conducive to the subsequent attachment of GO, and to reduce the interface resistance between the electrode and the electrolyte to a certain extent, promote the rapid and stable transfer of charge, and thus achieve a more compact loading; finally, it was ultrasonically cleaned with deionized water for 3 times, each time for 10 min; and vacuum dried to obtain the pretreated nickel foam sheet for use;

[0042] (2) Using deionized water as the dispersion medium of GO, a 0.2 mg / ml GO suspension was prepared for later use;

[0043] (3) The pretreated nickel foam sheet was used as the cathode, and parallel platinum sheets (10 mm × 20 mm × 1 mm) of equal area were placed on both sides of the cathode. A DC power supply with a constant voltage of 140 V was used for cathode electrophoretic deposition for 15 min to prepare NF loaded with GO;

[0044] (4) The GO-loaded NF was transferred to a 100 ml polytetrafluoroethylene reactor filled with ethylene glycol solution, reduced at 140 °C for 14 h, and then washed with deionized water several times to obtain a heterogeneous E-Fenton cathode material.

[0045] Scan the nickel foam before graphene loading, and its SEM image is as follows Figure 1 As shown in Figure 1, nickel foam has a mesh structure and a smooth surface before modification. The nickel foam loaded with graphene is scanned, and its SEM image is shown in Figure 1. Figure 2 As shown, it can be seen that the surface of the nickel foam is fully loaded with flaky graphene sheets after graphene modification, forming a good protective film and increasing the surface area of ​​the nickel foam. Figure 3 This is the SEM / mapping combination image of nickel foam after graphene loading. It can be seen that graphene is evenly loaded on the surface of the network nickel foam and the loading is successful. Figure 4 This is the mapping diagram of graphene loaded with nickel foam. The carbon elements are evenly distributed in the figure. Figure 2 It can be seen that the graphite oxide is hydrothermally reduced into graphene sheets and evenly loaded on the surface of the nickel foam to form a protective film, while increasing the conductivity and surface area of ​​the nickel foam. Figure 5 Figure 3 is the RhB removal rate curve before and after the nickel foam electro-Fenton cathode loading. It can be seen from the figure that the RhB 30min removal rate of the nickel foam cathode electro-Fenton cathode before graphene loading is less than 80%, and the RhB 30min removal rate of the nickel foam electro-Fenton cathode after graphene modification reaches 100%, and the removal effect is greatly improved.

[0046] Test Example 1

[0047] The cathode material prepared in Example 1 is used to remove the organic dye RhB

[0048] Degradation reaction conditions of RhB:

[0049] 8V voltage, electrode spacing 2cm, electrolyte 0.35mol / LNa2SO4, treatment time 30min, cathode is GA-NF (10mm*20mm*2mm), anode is Pt sheet (10mm*20mm*1mm), RhB 10mg / L.

[0050] The removal rate is 100% in 30 minutes. Figure 5 Middle curve GA-NF-1.

[0051] Test Example 2

[0052] RhB removal rate experiment before nickel foam loading

[0053] Degradation reaction conditions of RhB:

[0054] 8V voltage, electrode spacing 2cm, electrolyte 0.35mol / LNa2SO4, treatment time 30min, cathode is NF (10mm*20mm*2mm), anode is Pt sheet (10mm*20mm*1mm), RhB 10mg / L.

[0055] The removal rate in 30 minutes is less than 80%. Figure 5 Middle curve NF.

[0056] In summary, the heterogeneous E-Fenton cathode material prepared by the method of the present invention can break through the limitation of the traditional E-Fenton pH, and the removal rate of organic dye (RhB) in 30 minutes under neutral conditions can reach more than 99% (see Figure 5 ), has the advantages of high reaction activity and good treatment effect, and does not require the addition of Fe ions and hydrogen peroxide, and no iron mud is produced during the reaction.

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Including but not limited to the following situations:

[0058] 1. Use foam ceramics or other conductors for loading, and load GO in the same way to improve its performance.

[0059] 2. Using drugs containing elements such as iron, cobalt, and nickel instead of graphene for loading may also improve its performance.

Claims

1. A method for preparing a heterogeneous E-Fenton cathode material, comprising: (1) placing the nickel foam sheet in an acetone solution for ultrasonic treatment, and then immersing it in a 10% H2SO4 solution for acid washing; finally, ultrasonically cleaning it with deionized water, and vacuum drying it to obtain a pretreated nickel foam sheet for use; (2) using deionized water as a dispersion medium for graphite oxide to prepare a graphite oxide suspension for later use; (3) using the pretreated nickel foam sheet as a cathode, placing parallel platinum sheets of equal area on both sides of the cathode, and performing cathode electrophoretic deposition with a DC power supply at a constant voltage to prepare a nickel foam sheet loaded with graphite oxide; (4) The nickel foam sheet loaded with graphite oxide is transferred to a polytetrafluoroethylene reactor with a volume of 100 ml and filled with ethylene glycol solution, and after high-temperature reduction, it is repeatedly washed with deionized water to obtain a heterogeneous E-Fenton cathode material.

2. The preparation method according to claim 1, wherein: The size of the nickel foam sheet in step (1) is 10 mm × 20 mm × 2 mm; The ultrasonic treatment time in the acetone solution is 20 min; The pickling time of the H2SO4 solution is 5 minutes.

3. The preparation method according to claim 1, wherein: The deionized water ultrasonic cleaning in step (1) is performed 3 times, and each cleaning time is 10 minutes.

4. The preparation method according to claim 1, wherein: The concentration of the graphite oxide suspension in step (2) is 0.2 mg / ml.

5. The preparation method according to claim 1, wherein: The size of the platinum sheet in step (3) is 10 mm × 20 mm × 1 mm; The constant voltage is 140 V and the deposition time is 15 min.

6. The preparation method according to claim 1, wherein: The high temperature reduction temperature of step (4) is 140° C. and the reduction time is 14 h.

7. A heterogeneous E-Fenton cathode material prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the heterogeneous E-Fenton cathode material according to claim 7 in treating refractory high molecular organic pollutants.

9. The use according to claim 8, comprising: In the application process of treating difficult-to-degrade high-molecular organic pollutants, the heterogeneous E-Fenton cathode material is used as the cathode, 0.1-3.0L / min of oxygen or air is introduced near the cathode, and the inert electrode is used as the anode. The treatment object is sewage or soil containing organic pollutants, and an electrolyte solution with a pH of 3-8 is added. The organic pollutants are treated by direct current electrolysis of 2-8V.

10. The use according to claim 9, wherein: The difficult-to-degrade high-molecular organic pollutants include: phenol, norfloxacin, sodium dodecylbenzene sulfonate, and p-nitrophenol.

Citation Information

Patent Citations

  • Quick preparation method for graphene / foamed nickel composite material electrode

    CN105914056A

  • Preparation method and application of three-dimensional porous MnO2 / graphene composite material

    CN108847358A

  • Foamed nickel and iron carbon combined biological filler and preparation method thereof

    CN108996662A

  • Preparation method of reduced graphene oxide membrane

    CN110117003A

  • Porous graphene oxide color-changing composite film and preparation method thereof

    CN111624245A